2 - Higher Education, Society, and Government: Changing Dynamics: Kenneth Prewitt - Kenneth Prewitt (Journal of Higher Education in Africa, 2004)
Reform strategies for Africa’s universities are adjusting to three macro-trends: market pressures, demographic forces, and changing donor perspectives. Market-like definitions of accountability with their related performance indi- cators—focused less on what is known than on how fast and effectively knowl- edge is transformed into technologies, skills, and economic growth—are gen- erating unprecedented institutional diversification in African higher education. This occurs as demographic forces threaten to deplete Africa of its most tal- ented students who, if given the chance, will migrate for training and work. In the growing international competition for students, the balance of trade will not favor Africa. Those donors who remain committed to Africa are searching for models in which Africa’s universities reposition themselves as indispens- able bridges between the national economy and the international knowledge economy. Ensuring that universities—despite market and demographic pres- sures—continue to promote the “public good” in higher education and ad- vanced research should be the strategy of choice.